Satisfaction with urban life-style in Zagreb: Differences between immigrants and domicile inhabitants - Kamenov, Željka; Stiperski, Zoran (1998)
The purpose of this study was to determine the degree of satisfaction with life in Zagreb and with the opportunities this town provides, with the special emphasis on possible differences between subjects born in Zagreb and those who were born elsewhere but came to live in Zagreb. For this purpose, a new questionnaire was designed. It contained, along with some other questions, a set of 12 iems considering opportunities provided in Zagreb: education, employment, health care, commerce, traffic, culture, entertainment, sport and recreation, social relations and physical emvironment. Subjects were asked to express their level of satisfaction with each opportunity on 4-point scale. They also had to choose three most important opportunities for themselves. The questionnaire was administered to a representative sample of adult inhabitants of Zagreb (N=748), 367 immigrants and 381 domicile residents. The ANOVA and discriminant analysis were conducted. The differences in general satisfaction, as well as those considering the specific opportunity, are discussed in relation to the relevant sample characteristics.
Projekt MZOS
ENG